(untitled) (Economic studies journal, 2020)
Ethics is one of the manifestations of social control of individuals and motivates them to reach their ends and a means to liberate them from their instincts and desires. Ethics is a common denominator among professions. The profession of education is one of the most honourable professions. It plays a large role in society. As the teacher no longer informs us, but became facilitator of the process of learning, and guidance, and guidance in the scientific, educational, and ethical aspects of the learner. The problem of the study is centred on the issue of applying ethical standards to the university education profession. The study aimed to identify the attitude of university members towards ethics of the university education profession from the point of view of faculty members at the Faculty of Economics, University of Tripoli. The results of the study showed that the proportion of the holders of the higher qualification of the Masters was the largest, the scientific specialization accounting for the largest percentage, and the degree of the lecturer was the largest percentage among the degrees. The results also showed that the levels of study axes of the ethical standards of the university education profession were above average from the point of view faculty of school.